Standards as a tool for teaching and assessing cross-curricular writing. Issue 2 (2nd April 2016) - Evensen, Lars Sigfred; Berge, Kjell Lars; Thygesen, Ragnar; Matre, Synnove; Solheim, Randi
ABSTRACT: The Berge et al. article in this volume presents the functional construct of writing that underlies summative and formative assessment of writing as a key competency in Norway. A functional construct implies that specific acts of writing and their purposes constrain what is a relevant selection among the semiotic resources that writing generally affords. In this article, we present the specific criteria that are currently being introduced in Norwegian teaching and assessment of writing, as well as selected aspects of their development. The article builds on an assumption that assessment criteria have such educational importance that even their origins, intellectual trajectories and underpinnings should be given attention in educational research. In this context, the article presents elements of a rare approach, in that national 'norms of expected proficiency' at politically predefined educational grade levels have been grounded in sustained collaboration with experienced teachers of writing across the curriculum, and may thus be viewed as yet unofficial 'standards'. In the first step, a combination of existing curricula and literature review of writer development was used to tentatively draft a first set of criteria for the grades included in a 2005 national test of writing (grades 4, 7, 10 and 11). In the second step, such criteria were developed through an iterative, long-term process where initial criteria were confronted with the judgements of experienced teachers. Through 'think aloud' assessment interviews, pairs of teachers across Norway were asked to assess specific cases of students' writings and voice criteria for their judgements, both within and across a series of domains. In the third step, interview transcripts were used to search for criteria used by several pairs of locally situated teachers across geographically distributed schools. Criteria thus identified were pooled into a refined set of 'national standards' that were subsequently tested out in everyday classroom contexts. On the basis of this confrontation with educational reality, the set has been further refined to form the version presented in this article . The Norwegian case raises a range of issues related to curriculum development, 'standards' and educational sustainability.